Comparative performance of pure vegetable oil and Al2O3 based vegetable oil during MQL turning of AISI 4130. (2020) - Gupta, Anjali; Kumar, Rajesh; Kumar, Harmesh; Garg, Harry
Abstract: The present study investigated the comparative performance of machining during turning of AISI4130 using pure Vegetable oil and Al2 O3 nano particles based Vegetable oil as a coolant considering average surface roughness as the response parameter. To prepare the nano cutting fluid, nano sized Al2 O3 solid particles (0.5% wt.) were dispersed in vegetable oil.Taguchi method was used to design the experiments, for three different input parameters viz. cutting speed, feed rate and depth of cut at three different levels. Experimental results reveal that the turning performance under Al2 O3 based nanofluids was better and about 27.3% improvement on the finish quality of work material was observed over pure oil based machining conditions.